The effect of conjugated linoleic acid supplementation in comparison with omega-6 and omega-9 on lipid profile: a graded, dose–response systematic review and meta-analysis of randomized controlled trials - Akhgarjand, Camellia; Tavakoli, Aryan; Samavat, Simin; Bagheri, Amir; Anoushirvani, Aliarash; Mirzababaei, Atieh; Amini, Mohammad Reza; Ghorbi, Mahmoud Dehghani; Valisoltani, Neda; Mansour, Asieh; Sajjadi-Jazi, Sayed Mahmoud; Ansar, Hastimansooreh; et al. (Frontiers in Nutrition, 2024)
Conjugated linoleic acid (CLA) is a geometrical isomer of linoleic acid, which claim antiinflammatory, anti-diabetic, anti-cancer, and anti-obesity properties. However, the studies reported inconstant results about the CLA-related effects on lipid profiles. As a result, a meta-analysis and systematic review was performed to survey the CLA supplementation-related effect on lipid profile including high-density lipoprotein (HDL), low-density lipoprotein (LDL), total cholesterol (TC), and triglycerides (TG). To identify the relevant research, a systematic comprehensive search was initiated on the medical databases Scopus and PubMed/Medline until December 2022. The overall effect size was estimated by weighted mean difference (WMD) and 95% confidence interval (CI), in a random effect meta-analysis. In the final quantitative analysis, the meta-analysis considered 35 randomized controlled trials (RCTs) with 1476 participants (707 controls and 769 cases). The pooled results demonstrated that CLA supplementation, compared to olive oil, significantly increased serum TG levels (WMD: 0.05 mmol/L; 95% CI: 0.01 to 0.1; P = 0.04; I2= 0.0%, P=0.91). With regard to TC level, CLA supplementation compared to placebo significantly reduced TC concentrations (WMD: -0.08 mmol/L; 95% CI: -0.14 to -0.02; P ˂ 0.001; I 2 = 82.4%).Moreover, the non-linear dose-response analysis indicated a decreasing trend of TC serum level from the 15 th -week duration of CLA supplementation compared to olive oil (Pnon-linearity= 0.01).The present meta-analysis and systematic review of 35 RCTs showed that the CLA intervention was able to raise the level of TG in comparison with olive oil; however, it can decrease TC level compared to placebo and olive oil.